Effect of explants density on the in vitro proliferation and growth of separated and cluster shoots of smooth cayenne pineapple (Ananas comosus L. Merr.) - Hamad, A.M.; Taha, R.M. (2009)
Multiplication rate was always used as the sole parameter for assessment of the optimal treatment for in vitro shoot formation. However, beside its effect on the shoot formation, different treatments had different impact on the production cost. Separated shoots and shoot cluster of different sizes (1, 2, 3 and 4 shoots per cluster) of Smooth cayenne pineapple were cultured at density of 1, 2, 3 and 4 separated shoots and 1 cluster on agar solidified full strength MS medium enriched with sucrose at 30 g L-1 and BAP at 2.25 mg L-1 for 2 months to investigate the effect of explants density and explant types on shoot formation per explant, total per liter and cost per shoot. Density of one separated shoot per culture resulted in the highest shoot formations per shoot (11 shoots) but lowest total shoot per liter (550 shoots) and highest cost per shoot (13 cents), while density of 4 shoots per culture resulted in lowest rate (4 shoots) but higher total per liter (1400 shoots) and lowest cost per shoot (10 cents). Cluster of two shoots had higher rate (7 shoots) and lower cost (16 cents) than cluster of 4 shoots (4 shoots and 20 cents) but both resulted in equal total shoot per liter (750 shoots). Separated shoot had higher shoot formation capacity, higher total per liter and lower cost per shoots than cluster of shoots and using of total per liter instead of rate per explant was the best parameter for selection of treatment of lower cost and higher shoots production. Â© 2009 Asian Network for Scientific Information.